Circular Migration and the Rights of Migrant Workers in Central and Eastern Europe The EU Promise of a Triple Win Solution - Vankova, Zvezda (IMISCOE Research Series, 2020)
By adopting a rights-based approach, this open access book sheds light on the different legal and policy instruments that have been adopted to implement circular migration policies in the EU and their consequences for the rights of migrant workers. It contributes to the understanding of the meaning of this concept in general, in the EU, as well as more specifically with regard to its Eastern neighbourhood. The book provides a comprehensive overview of the formation and implementation of the EU's circular migration approach that has developed through both EU and national instruments on the basis of comparative case study analysis of Bulgaria and Poland's migration law and policy. Furthermore, by applying legal empirical research methods, it draws conclusions about the policy outcomes from the implementation of the various migration instruments falling under the circular migration umbrella and shows the consequences for the rights of migrant workers as a result of the application of different policy options. Along with its value to an academic audience, the book can be used by policy makers at the EU, international and national level as well as international organisations and NGOs working in the field of migration law and policy.